Secure Research at scale: IJPDS (2017) Issue 1, Vol 1:171, Proceedings of the IPDLN Conference (August 2016) - Thompson, Simon (International Journal of Population Data Science, 2017)
ABSTRACT Background As part of an initiative funded by FARR institute, Swansea University Health Informatics Unit embarked on the creation of the UK Secure e-Research Platform (UKSeRP) to both build on the experience developed by the SAIL databank over many years and to create an infrastructure that can support, at scale, multiple national research programmes. Method The system was created utilising the in-house technical staff and combines multiple vender solutions all orchestrated through bespoke developments. The same team also developed the National Research Data Appliance (NRDA) and elements of this initiate were integrated into the core of this development. Results The system went live at the end of February 2016 and is already supporting five national level research programmes. The presentation will show now the system is architected and how it evolved over time as additional opportunities arose. It is imperative to both provide common architecture and systems that can scale to meet the research programmes needs and yet still allow for additional unique aspects to be provisioned that deliver against the programmes research goals and differing governance models. The platform has gained an ISO 27001 accreditation which provided clear control and management over information security but also allows programmes utilising the platform to inherit these key controls and if desirable to gain their own accreditation easier, as the SAIL Databank has demonstrated. The platform has an ambitus road map and is currently adding imaging capabilities supported by an imaging processing pipeline. Genomics handling, processing and analysis capabilities are being added in the next couple of months. Conclusion The demand for UKSeRP has been higher than initially envisaged and the possible use cases are constantly being imagined. We are also introducing an entry level UKSeRP to support individual projects and their requirements.